Die neueren Quellen von Persecutio Hungaricae - Csorba, Dávid (Acta Neerlandica, 2026)
The study focuses on the history and historiography of the Hungarian Galley Slaves. The publication of their story by the Western European press made a huge impact on international Calvinism. In Hungary it went the opposite way, mainly for historical reasons. A manuscript and its large amount of copies built a great legacy, thanks to the historical research for the original documents (mentioned in texts by Bálint Kocsi Csergő and Ferenc Otrokocsi Fóris) between the 17th and 20th century. Thus, the attitude of the Galley Slaves indeed became a decisive image of Hungarian, reformed identity.